1989
DOI: 10.1080/15287398909531360
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic study of insecticide exposures, obesity, and risk of bladder cancer in household dogs

Abstract: A case-control study of household dogs was conducted to determine if exposure to sidestream cigarette smoke and chemicals in the home, use of topical insecticides, and obesity are associated with the occurrence of bladder cancer. Information was obtained by interview from owners of 59 dogs with transitional-cell carcinoma of the bladder and 71 age- and breed size-matched control dogs with other chronic diseases or neoplasms. Bladder cancer risk was unrelated to sidestream cigarette smoke and household chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 6 publications
3
90
0
4
Order By: Relevance
“…6 Bladder cancer risk was not related to sidestream cigarette smoke and household chemical exposure. There was, however, a significant, dose-related association between topical application of flea and tick dip and TCC.…”
Section: Insecticides Obesity and Sexmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Bladder cancer risk was not related to sidestream cigarette smoke and household chemical exposure. There was, however, a significant, dose-related association between topical application of flea and tick dip and TCC.…”
Section: Insecticides Obesity and Sexmentioning
confidence: 99%
“…In addition, risk of TCC was higher in dogs living near marshland sprayed with insecticide(s). 6 The authors speculated that the ''inert'' ingredients, accounting for Ͼ95% of the total product, were the probable carcinogens in these products.…”
Section: Insecticides Obesity and Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…A marginal excess risk of lung cancer was observed in dogs aged 10 years or less and exposed to household tobacco smoke in one study (Reif et al, 1992). Risk of bladder cancer in dogs was not related to exposure to household cigarette smoke in another study (Glickman et al, 1989).…”
Section: Observational Studies Of Companion Animalsmentioning
confidence: 99%
“…For example, obesity was identified as a risk factor in association with pesticides for the development of transitional cell carcinomas in Scottish Terrier dogs. 29 Thus, maintaining ideal body weight may also reduce the risk for the development of a variety of tumors and reduce the incidence of pancreatitis, diabetes mellitus, and bone and joint diseases. Recently, studies of lifelong diet restriction in Labrador Retrievers indicated a 1.8-year longer survival in the leaner dogs.…”
Section: Dietary Compounds and Cancer Chemopreventionmentioning
confidence: 99%